Tree of life 1 - reverse section - Unidentified artist (Colorado State University. Libraries, 1980)
Reverse of a section of the Tree of Life 1.
This item was part of an exhibition at the Avenir Museum of Design and Merchandising titled Kuna Molas: Sewn Stories and the Interplay of Tradition and Change, August 18, 2014-July 31, 2015.
Cotton; 3 layers (maroon, orange, black); reverse and direct appliqué, embroidery.
Keywords: Molas -- Panama; Appliqué -- Panama; Embroidery -- Panama